Effects of replacing maize with mango seed kernel meal on performance, carcass characteristics and economic of production of weaner rabbits - Saleh, N.; M. Bello, K. (Scientific Journal of Zoology, 2015)
An experiment was conducted to examine the effect of replacing maize with mango seed kernel meal (MSKM) in the diets of Weaner rabbit on performance, carcass characteristics and economic of production. Twenty mongrel rabbits were randomly allocated to four diets in which mango seed kernel meal replaced maize at 0, 33.33, 66.67 and 100% level designed as diets 1, 2, 3 and 4 respectively. The daily feed intake (42.75-49.76), daily weight gain (8.75-9.72) and feed conversion ratio (4.64-5.19) obtained were not significantly (P<0.05) affected by the dietary levels of mango seed kernel meal. Carcass yield and weight of organs expressed as percentage of live weight did not significantly differ between the treatment means. The cost in naira per kilogram gain was highest on diet 1 (0%MSKM) and lowest on diet 4 (100% MSKM) having N338.84 and 245.58 respectively. The result indicates that mango seed kernel meal can replace maize at 100% level in the diet of Weaner rabbit with better performance and tremendous reduction in feed cost.